Measuring Fate and Rate of Single‐Molecule Competition of Amplification and Restriction Digestion, and Its Use for Rapid Genotyping Tested with Hepatitis C Viral RNA1. (2nd June 2014) - Sun, Bing; Rodriguez‐Manzano, Jesus; Selck, David A.; Khorosheva, Eugenia; Karymov, Mikhail A.; Ismagilov, Rustem F.
Abstract We experimentally monitored, at the single‐molecule level, the competition among reverse transcription, exponential amplification (RT‐LAMP), and linear degradation (restriction enzymes) starting with hepatitis C viral RNA molecules. We found significant heterogeneity in the rate of single‐molecule amplification; introduction of the restriction enzymes affected both the rate and the "fate" (the binary outcome) of single‐molecule amplification. While end‐point digital measurements were primarily sensitive to changes in fate, the bulk real‐time kinetic measurements were dominated by the rate of amplification of the earliest molecules, and were not sensitive to fate of the rest of the molecules. We show how this competition of reactions can be used for rapid HCV genotyping with either digital or bulk readout. This work advances our understanding of single‐molecule dynamics in reaction networks and may help bring genotyping capabilities out of clinical labs and into limited‐resource settings.